MIKROALGA SEBAGAI SUMBER BIOMASA TERBARUKAN: TEKNIK KULTIVASI DAN PEMANENAN - Ariyanti, Dessy; Handayani, Noer Abyor (METANA, 2010)
Abstract   For millennia, aquatic environment has been a source of food, minerals, and natural products to fulfill human’s need. In order to resolved problem due to increment of population, the development of product microalgae based which is one of renewable resource absolutely needed.   There are two important processes in biotechnology of microalgae, microalgae cultivation and harvesting. Common cultivation methods used in growing microalgae are open raceway pond system and closed photobioreactor system. While harvesting methods used is flocculation, centrifugation and filtration. This paper described briefly the methods used in cultivation and harvesting of microalgae.   Keywords: microalgae, cultivation, harvesting